Single-Cell Transcriptomic Analysis Reveals the Crosstalk Propensity Between the Tumor Intermediate State and the CD8+ T Exhausted State to be Associated with Clinical Benefits in Melanoma - Zhu, Jiali; Yan, Min; Yan, Haoteng; Xu, Liwen; Jiang, Zedong; Liao, Gaoming; Zhou, Yao; Liu, Wei; Liang, Xin; Li, Xia; Xiao, Yun; Zhang, Yunpeng (Frontiers in Immunology, 2022)
Heterogeneous crosstalk between tumor cells and CD8+ T cells leads to substantial variation in clinical benefits from immunotherapy in melanoma. Due to spatial distribution and functional state heterogeneity, it is still unknown whether there is a crosstalk propensity between tumor cells and CD8+ T cells in melanoma, and how this crosstalk propensity affects the clinical outcome of patients. Using public single-cell transcriptome data, extensive heterogeneous functional states and ligand-receptor interactions of tumor cells and CD8+ T cells were revealed in melanoma. Furthermore, based on the association between cell-cell communication intensity and cell state activity in a single cell, we identified a crosstalk propensity between tumor intermediate state and CD8+ T exhausted state. This crosstalk propensity was further verified by pseudo-spatial proximity, spatial co-location, and intra/inter-cellular signal transduction network. At the sample level, tumor intermediate state and CD8+ T exhausted state synergistically indicated better prognosis and both reduced in immunotherapy resistant samples. The risk groups defined based on these two cell states could comprehensively reflect tumor genomic mutations and anti-tumor immunity information. The low-risk group had a higher BRAF mutation fraction as well as stronger antitumor immune response. Our findings highlighted the crosstalk propensity between tumor intermediate state and CD8+ T exhausted state, which may serve as a reference to guide the development of diagnostic biomarkers for risk stratification and therapeutic targets for new therapeutic strategies.